Occupational heat exposure alone does not explain chronic kidney disease of uncertain aetiology (CKDu) in Sri Lanka - P. Mangala C.S. De Silva; E.M.D.V. Ekanayake; T.D.K.S.C. Gunasekara; W. A. K. G Thakshila; P.M.M.A. Sandamini; P.A. Abeysiriwardhana; K.G.D. Nishara; Akila Harishchandra; P.H. Chaminda De Silva; Nipuna Siribaddana; E.P.S. Chandana; S. S Jayasinghe; et al. (Elsevier, 2022)
Aim: Chronic kidney disease of uncertain aetiology (CKDu) is an emerging health concern in tropical farming communities. The role of occupational heat exposure as a potential driver of CKDu remains debated. Our study examines occupational heat exposure and kidney health in three occupational groups in Sri Lanka. Methodology: We recruited participants from three occupational groups from three climatic zones; fisherfolk from the dry and intermediate zones (N = 225), paddy farmers from the intermediate zone (N = 180) and tea plantation workers from the wet zone (N = 70). Serum creatinine, cystatin-C, urea and uric acid, estimated glomerular filtration rate and urinary albumin-creatinine ratio were used as diagnostic criteria of impaired renal function. Results: CKDu susceptibility was at the highest among farmers (13.33 %), with a significant difference compared to the fisherfolk (5.36 %; p = 0.0003). Among the plantation workers, CKDu susceptibility was 5.71 %, and it was not significantly different compared to the farmers (p = 0.087) and the fisherfolk (p = 0.427). Despite higher exposure to heat stress and dehydration, as indicated by the highest simplified wet bulb globe temperature (sWBGT) in the work environments, fisherfolk reported the lowest CKDu susceptibility, while farmers and workers with low to moderate heat exposure showed an increased incidence of abnormal renal function. Further, a multivariable regression analysis identified a significant effect of occupation (p = 0.005), agrochemical exposure (p = 0.001) and age (p = 0.001) on the likelihood of CKDu susceptibility while the sWBGT in the working environments showed no significant effect (p = 0.227). Conclusion: With the evidence from our findings, heat exposure alone does not appear to be the leading driver of CKDu in Sri Lanka, suggesting that the nephropathy is more likely to be associated with occupational risks such as agrochemical exposures.